MORPHOLOGICAL AND CLINICAL INDICATIONS OF COMPLICATIONS OF CARDIOVASCULAR DISEASE ARCUS SENILIS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Among the complications of cardiovascular disease, arcus senilis occupies a special place. This condition is often associated with old age and is considered as a sign of complex pathological processes that occur as a result of disorders of blood vessels and heart function. Arcus senilis is a white or gray circle that appears on the edge of the eye, especially around the blackout, and its morphological and clinical indications help to better understand the processes associated with cardiovascular disease.